Modelling and Estimation of Regional Consumption Functions: A Case for the Russian Far East - Artyom Gennadyevich Isaev (Prostranstvennaâ Èkonomika)
This paper estimates regional consumption functions based on the error correction model on the basis of the 2000–2002 data on real disposable income and consumption expenditures for 11 regions of the Far Eastern Federal District of Russia. The work reveals the existence of short-term and long-term relationships between the dynamics of income and consumption of the population, which are important for the generation of multiplicative effects in the economies of the corresponding regions. It is found that 7 regions of the Russian Federation (the Republic of Buryatia, Zabaykalsky Krai, Primorsky and Khabarovsk Krais, Amur and Sakhalin Oblasts, as well as the Jewish Autonomous Oblast) are characterized by the presence of both statistically significant short-term relationships between changes in income and changes in consumption, and long-term equilibrium ratios between income and consumption. The indicators of short-term marginal propensities to consume, which are the basis of regional multipliers of autonomous expenditures, have been calculated. For the Republic of Sakha (Yakutia) the data reveals a statistically significant short-term relationship between income and consumption in the absence of a long-term relationship between the indicators. For Kamchatka Krai, Magadan Oblast and Chukotka Autonomous Okrug, the absence of both short-term and long-term interrelations between income and consumption was confirmed, and, consequently, the absence of potential for generation of other multiplier effects in the economy, except for those due to purely inter-sectoral relations